Self-assembled nanoparticles: A new platform for revolutionizing therapeutic cancer vaccines - Shi, Tianyu; Sun, Mengna; Lu, Changchang; Meng, Fanyan (Frontiers in Immunology, 2023)
Cancer vaccines have undergone a prosperity in the past decade. Based on in-depth analysis of tumor antigen genomics, many therapeutic vaccines have already entered clinical trials for multiple cancers, including melanoma, lung cancer, head and neck squamous cell carcinoma, which have demonstrating impressive tumor immunogenicity and anti-tumor activity. Recently, vaccines based on self-assembled nanoparticles are being actively developed as cancer treatment and the feasibility has been confirmed in both mice and humans. In this review, we summarize recent therapeutic cancer vaccines based on self-assembled nanoparticles. We describe the basic ingredients for self-assembled nanoparticles, and how them enhance vaccine immunogenicity. We also discuss the novel design method for self-assembled nanoparticles that pose as promising delivery platform for cancer vaccines, and the potential in combination with multiple therapeutic approaches.